Gender policy in Middle East and North Africa in the aftermath of Arab Spring (Journal of Philosophy Culture and Political Science, 2019)
In this article the authors made an attempt to analyze gender policy in Middle East and North Africa in the immediate aftermath of the Arab spring. Comparative analysis is conducted based on existing statistical data and sociological polls. Key tendencies of the current situation of women are identifi ed, as well as public policy is defi ned for several countries of the region. Key areas of concerns and gaps, requiring urgent state attention, are described. The authors also made an attempt to streamline effective directions of work for consistent im-plementation of the gender policy, advancing women’s human rights and increasing their political participation in the context of current reforms and transformations. Keywords: Public policy, gender relationships, policy, democratization, discrimination of women, women’s human rights, women’s political participation, globalization, Arab spring.